Description of medusa shrimp Latreutes anoplonyx Decapoda: Caridea, Hippolytidae) ) Kemp, 1914 in northwest Arabian Gulf - Al-Maliky, Tariq H. Y. (Iraqi Journal of Aquaculture, 2021)
Shrimp Latreutes anoplonyx sample were collected from the northwest Arabian Gulf that found symbiotic interaction with the Medusa white Rhizostoma sp.. The diagnostic feature of the species is the present of one tooth on dorsal region of the carapace. The rostrum longer than antennular and flagella. The rostrum in the male is curved to down ward above the eye, while in the female more wider and curved upward. the teeth found on both sides of the rostrum, about 9 – 16 on dorsal side and very high and smooth, while in ventral side they were between 7 – 10 and more distance in the mid and high density in the top. The largest for female was 4 cm in length and the average shrimp lengths were between 1.2 – 4.0 cm.